Socioeconomic Impact of SG 2000 Quality Protein Maize (QPM) Technology Delivery on Beneficiaries in Bauchi and Gombe States - L. J, Gizaki; Madukwe, M. C. (European Scientific Journal, ESJ, 2019)
The study assessed the impact of SG – 2000 QPM technology adoption on beneficiaries in Bauchi and Gombe States, Nigeria. Specifically, the study sought to determine the socioeconomic characteristics of the beneficiaries, identify beneficiaries sources of information on maize production, assess beneficiaries’ perception of the project, assess the impact of QPM technology adoption on the socioeconomic life of beneficiaries and identify constraints encountered by the beneficiaries in technology adoption. Purposive sampling was used in sampling 90 beneficiaries and 90 non- beneficiaries’ farmers to give a total of 180 from 10 Local Government Areas where maize is cultivated. The instrument for data collection was a structured interview schedule developed on a 3 – point Likert – type scales. Mean, percentage, t – test and factor analysis were used for data analysis. The study show that the project made a significant (P ≤ 0.05) impact on the project participants in the following socioeconomic possessions: number of milling machine (t = 11.331), quantity of maize harvested (t = 2.794), number of motorcycle owned (t = 4.040), number of wrist watch owned (t = 3.861), number of associations/clubs belonged (t = 3.038) and the number poultry birds owned (t = 2.071) in Gombe State. While, in Bauchi State, the project made significant (P ≤ 0.05) impact on number of ceiling/fans owned (t = 2.783), number of radios owned (t = 1.08), number of television owned (t = 1.457) and the number of cattle owned (t = 2.493). The major challenges encountered by the beneficiaries in technology adoption were socioeconomic, farm inputs, poor policy support and production related constraints. The study recommended that SG – 2000 QPM technology delivery should ensure timely distribution of inputs such as fertilizers, herbicides and subsidies on farm inputs. In addition, modern farm implements such as tractor should be made available to the beneficiaries to reduce drudgery associated with simple farm tools and to increase farm size per farmer.